Dual Development Direction of Small Sea Ports on The Example of the South Baltic Sea - Dariusz KLOSKOWSKI; Weronika KOSEK (Communications of International Proceedings, 2024)
The seaport remains a multidimensional system encompassing economic functions, infrastructure, geographical location, trade, transport technologies, and specific port management practices. The development of small seaports involves achieving higher levels of port performance. To accomplish this, it is necessary to consistently and continuously adapt seaports to the exponential changes in economic factors (such as market dynamics and competition), institutional frameworks, legal requirements, and operational demands. The primary goal of this study was to diagnose the issue of the government's low interest in developing smaller ports in favor of large port complexes located along the central coast of Poland. The duality related to the direction of development of small seaports on the Central Coast of Poland, which influence the final shape of the volume of maritime transport in Poland is an important issue that should be taken into account. The selected research area, i.e. the Polish South Baltic Sea and the so-called seaports agricultural hinterland: Kołobrzeg, Darłowo and Ustka, fits into the research topic, mainly due to the existence of high development potential of ports, which is not fully used. The research focused on the seaports of Kołobrzeg, Darłowo, and Ustka, situated within the coastal communes of Central Pomerania. Additionally, the indicated area is a strategic element in the predictive approach of building a new transfer channel for goods to Southern European countries. Due to the limitations related to the selection of literature related to the elements of port transformation, research methods were used: source data analyses, document and statistical data studies, as well as cause-and-effect analyses.
Keywords: Seaport; Port Functions; Seaside Space.